Social Media Engagement for Urology Journals— A Correlation Analysis of Traditional and Social Media Metrics - Wei Zheng So; Ho Yee Tiong; Vineet Gauhar; Daniele Castellani; Jeremy Yuen-Chun Teoh (Société Internationale d’Urologie Journal)
IntroductionThe growing adoption of social media (SoMe) by the scientific community has cemented the role of SoMe in information dissemination and engagement of academic work. The objective of this study is to evaluate the relationship between traditional and alternative SoMe metrics of urology journals. MethodsUrology journals listed on the SCImago Journal & Country Rank (SJR) electronic portal were selected and data pertaining to traditional metrics were collected. Official SoMe platforms of eligible journals were identified and indicators of online activity were recorded. Correlations between traditional metrics (SJR, h-index, and Scopus CiteScore) and social metrics were performed via Spearman rank-order correlation. ResultsOf 107 journals, 54.2% of journals had at least one form of SoMe presence. The median SJR (0.535 versus 0.334, P = 0.005), h-index (34 versus 20, P = 0.001), and Scopus CiteScore (3.25 versus 2.20, P = 0.014) were significantly higher among journals with SoMe networks. All 3 traditional indicators demonstrated strong global correlations with various Twitter-based metrics (rs = 0.428 to 0.571). In particular, SoMe journals with more than 3000 citations in the previous 3 years also displayed very strong correlations between all 3 traditional metrics and alternative social metrics (rs = 0.714 to 0.821). ConclusionsJournals with SoMe presence had significantly higher traditional metric values (SJR, h-index, and CiteScore) compared to journals without SoMe presence. Strong, positive correlations between citation-based and alternative social metrics were also observed. Alternative social metrics may be harnessed as supplemental indicators of a journal’s scientific impact.